A Competitive Model of Worker Replacement and Wage Rigidity - Andy Snell; Jonathan Thomas; Zhewei Wang (Center for Economic Studies and ifo Institute (CESifo), 2014)
We adapt the models of Menzio and Moen (2010) and Snell and Thomas (2010) to consider a labour market in which firms can commit to wage contracts but cannot commit not to replace incumbent workers. Workers are risk averse, so that there exists an incentive for firms to smooth wages. Real wages respond in a highly non-linear manner to shocks, exhibiting downward rigidity, and magnifying the response of unemployment to negative shocks. We also consider layoffs and show that for a range of shocks labor hoarding occurs while wages are cut. We argue these features are consistent with recent evidence.
Keywords: E32; J41; 330; labour contracts; business cycle; unemployment; labour hoarding; downward rigidity; cross-contract restrictions